A biomethane solution for domestic cooking in Thailand - Suwansri,S. (Elsevier, 2015)
This paper is concerned with the process of switching from non-renewable LPG to renewable biomethane for domestic cooking in Thailand. Most domestic stoves in Thailand use liquid petroleum gas (LPG), supplied in portable tanks. Switching to biomethane requires a method of (a) biomethane production, (b) biomethane storage and (c) stove modification to allow biomethane combustion. This paper will outline a solution to each of these three hurdles. A production plant was developed, a storage and delivery solution was designed and a methodology was developed and implemented for converting stoves for biomethane use. The results show that biomethane can be produced, delivered and combusted safely and efficiently in domestic Thai stoves. These results provide a roadmap for certain local communities to utilize renewable energy in a sustainable fashion. © 2014 Elsevier Ltd.